The Influence of Science, Technology and Society Learning Models on Value-Natured Energy Concepts on Student Learning Outcomes - Nukhbatul Bidayati Haka; Ady Purwoto (CV. Get Press Indonesia, 2024)
Science education plays a vital role in the development of science and technology, especially in an era that demands the integration of science, technology, and society. The Science, Technology, and Society (STM) learning model provides a holistic approach to teaching energy concepts by connecting scientific knowledge with social contexts and value considerations. This study aims to examine the effect of the STM learning model on students’ learning outcomes related to value-based energy concepts. The research employed a quasi-experimental design using a one-group pretest posttest method. The STM learning model was applied by linking energy topics with real-life issues and societal values. Data were collected through learning outcome tests and student response questionnaires. The results indicate that students responded positively to the implementation of the STM model, with 40% of students showing the highest level of positive response. However, student interest in conventional physics learning activities remained the lowest response indicator.The findings suggest that integrating societal and value aspects into energy instruction can enhance student engagement and conceptual understanding. The STM learning model helps bridge theoretical knowledge with its relevance to daily life. To further improve student interest, the use of varied instructional strategies such as discussions and field observations is recommended to create a more meaningful learning environment.